Corrosion-resistant bolt and preparation method thereof
By adjusting the composition and structure of the bolt body, adding elements such as Zn, Nb, V, and spraying modified mica powder and other materials on the surface, the problem of low bolt strength is solved and bolts with high mechanical strength and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411592734.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
AI Technical Summary
The existing bolts have low strength, which is difficult to meet the high mechanical strength requirements of modern industry for mechanical fasteners.
By adjusting the composition of the bolt body, adding elements such as Zn, Nb, V, etc. to improve the microstructure, and spraying modified mica powder and other materials on the surface to form an anti-corrosion layer to improve the strength and corrosion resistance of the bolts.
It significantly improves the tensile strength and corrosion resistance of bolts, which can better meet the high mechanical strength and corrosion resistance requirements of modern industry for mechanical fasteners.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fasteners, and in particular to a corrosion-resistant bolt and a preparation method thereof. Background Art
[0002] Bolts are a common mechanical fastener that plays a vital role in various fields. The structure of a bolt usually consists of a head and a screw. There are many shapes of the head, such as hexagonal head, round head, square head, etc., which are used to facilitate the use of tools for tightening and disassembly. The screw usually has threads, which are used in conjunction with the nut to achieve the functions of connection and tightening. Bolts are also made of a variety of materials, including carbon steel, alloy steel, stainless steel, etc., to meet different use environments and requirements. In modern industry, bolts are widely used. In the field of mechanical manufacturing, bolts are used to connect components of various mechanical equipment to ensure the normal operation of the equipment. In construction projects, bolts are used to connect steel structures, concrete structures, etc. to ensure the stability and safety of buildings. In the field of transportation, bolts are used to connect components of vehicles such as cars, trains, and airplanes, and bear huge loads. Therefore, as an important mechanical fastener, bolts need to have high mechanical strength to ensure the overall continuity and stability of the structure. Summary of the invention
[0003] The invention provides a corrosion-resistant bolt and a preparation method thereof, which solves the problem of low bolt strength in the related art.
[0004] The technical solution of the present invention is as follows: The present invention provides a corrosion-resistant bolt, comprising a bolt body and an anti-corrosion layer on the surface of the bolt body, wherein the bolt body is composed of the following components by weight percentage: C 0.2%-0.4%, Si 0.3%-0.6%, Mn 1.0%-2.2%, Ni1.5%-2.5%, Cr 0.1%-0.5%, Mo 0.02%-0.2%, Zn 0.001%-0.5%, Nb 0.005%-0.5%, V 0.01%-0.1%, and the rest is iron and inevitable impurities.
[0005] As a further technical solution, the weight ratio of the sum of the weights of Zn and Nb to the weight of V is 3-5:1.
[0006] In the present invention, the weight of Zn and Nb and the weight ratio of Zn and Nb to V are limited to 3-5:1, thereby further improving the strength of the bolt.
[0007] As a further technical solution, the weight ratio of the Zn to the Nb is 2:1.
[0008] In the present invention, under the condition that the weight ratio of Zn and Nb to V is 3-5:1, and the weight ratio of Zn to Nb is limited to 2:1, the strength of the bolt is further improved.
[0009] The present invention also provides a method for preparing a corrosion-resistant bolt, comprising the following steps: S1, after preparing the materials according to the components, smelting and casting to obtain a steel ingot; S2, the steel ingot is forged, heat treated, drawn and threaded to obtain a bolt body; S3, mixing the raw materials for the anti-corrosion layer, spraying them on the surface of the bolt body, and obtaining the corrosion-resistant bolt after drying.
[0010] As a further technical solution, the raw materials of the anti-corrosion layer include the following components in parts by weight: 40-50 parts of aqueous acrylic emulsion, 1-3 parts of zinc sulfate, 3-5 parts of isocyanate, 1-3 parts of hydroxypropyl methylcellulose, 3-5 parts of dimethylaniline, 6-9 parts of strontium titanate, 10-15 parts of zirconium oxide, 20-30 parts of mica powder, 0.5-0.8 parts of propylene glycol butyl ether, and 1-2 parts of vinyl triethoxy silane.
[0011] As a further technical solution, the mica powder is modified mica powder; the modified mica powder is mica powder modified by 2-cyclohexylaminoethanesulfonic acid.
[0012] In the present invention, the mica powder is modified by using 2-cyclohexylaminoethanesulfonic acid, thereby further improving the corrosion resistance of the bolt.
[0013] As a further technical solution, the added amount of the 2-cyclohexylaminoethanesulfonic acid is 3% to 5% of the mass of the mica powder.
[0014] As a further technical solution, the preparation method of the modified mica powder comprises the following steps: dissolving 2-cyclohexylaminoethanesulfonic acid in methanol, adding mica powder for modification, and obtaining the modified mica powder through drying.
[0015] As a further technical solution, the modification temperature is 50-60° C., and the modification time is 3-6 hours.
[0016] As a further technical solution, the heat treatment includes normalizing, quenching and tempering.
[0017] As a further technical solution, the normalizing temperature is 850~870℃, and the normalizing time is 60~80min; the quenching temperature is 810~830℃, and the quenching time is 50~60min; the tempering temperature is 570~580℃, and the tempering time is 60~70min.
[0018] The working principle and beneficial effects of the present invention are: In the present invention, the corrosion-resistant bolt consists of a bolt body and an anti-corrosion layer on the surface of the bolt body, wherein the components of the bolt body are adjusted in composition and proportion so that the components cooperate with each other and work together to improve the strength of the bolt, and the addition of Zn, Nb and V improves the microstructure of the bolt body and further improves the strength of the bolt body. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In the following embodiments and comparative examples: Mica powder, particle size: 800 mesh; water-based acrylic emulsion, model: RESIN HF-05A; isocyanate, model: M20S.
[0021] Ferrosilicon alloy, silicon content is 75wt%; ferromolybdenum alloy, molybdenum content is 70wt%; ferrovanadium alloy, vanadium content is 50wt%; ferromanganese alloy, manganese content is 68wt%; ferrochromium alloy, chromium content is 60wt%; ferroniobium alloy, niobium content is 40wt%.
[0022] Example 1 A corrosion-resistant bolt comprises a bolt body and an anti-corrosion layer on the surface of the bolt body, wherein the bolt body is composed of the following components by weight percentage: C 0.2%, Si 0.3%, Mn 1.0%, Ni 1.5%, Cr 0.1%, Mo 0.02%, Zn 0.001%, Nb 0.005%, V 0.01%, and the rest is iron and unavoidable impurities; The anticorrosive layer raw materials include the following components in parts by weight: 40 parts of water-based acrylic emulsion, 1 part of zinc sulfate, 3 parts of isocyanate, 1 part of hydroxypropyl methylcellulose, 3 parts of dimethylaniline, 6 parts of strontium titanate, 10 parts of zirconium oxide, 20 parts of mica powder, 0.5 parts of propylene glycol butyl ether, and 1 part of vinyl triethoxy silane; The method for preparing the corrosion-resistant bolt comprises the following steps: S1. Mix carbon powder, ferrosilicon alloy, ferromanganese alloy, nickel powder, ferrochrome alloy, zinc block, ferrovanadium alloy, ferromolybdenum alloy and ferroniobium alloy according to the ingredients, and smelt and cast them to obtain steel ingots; S2. After forging, the steel ingot is normalized at 850°C for 80 minutes, quenched at 810°C for 60 minutes, tempered at 570°C for 70 minutes, and then drawn and threaded to obtain the bolt body; S3. Mix the raw materials for the anti-corrosion layer, spray them on the surface of the bolt body, and obtain the corrosion-resistant bolt after drying.
[0023] Example 2 A corrosion-resistant bolt comprises a bolt body and an anti-corrosion layer on the surface of the bolt body, wherein the bolt body is composed of the following components by weight percentage: C 0.3%, Si 0.4%, Mn 1.7%, Ni 2.0%, Cr 0.3%, Mo 0.11%, Zn 0.1%, Nb 0.2%, V 0.03%, and the remainder is iron and unavoidable impurities; The anticorrosive layer raw materials include the following components in parts by weight: 45 parts of water-based acrylic emulsion, 2 parts of zinc sulfate, 4 parts of isocyanate, 2 parts of hydroxypropyl methylcellulose, 4 parts of dimethylaniline, 8 parts of strontium titanate, 12 parts of zirconium oxide, 25 parts of mica powder, 0.7 parts of propylene glycol butyl ether, and 1.5 parts of vinyl triethoxy silane; The method for preparing the corrosion-resistant bolt comprises the following steps: S1. Mix carbon powder, ferrosilicon alloy, ferromanganese alloy, nickel powder, ferrochrome alloy, zinc block, ferrovanadium alloy, ferromolybdenum alloy and ferroniobium alloy according to the ingredients, and smelt and cast them to obtain steel ingots; S2. After forging, the steel ingot is normalized at 860°C for 70 minutes, quenched at 820°C for 55 minutes, tempered at 570°C for 70 minutes, and then drawn and threaded to obtain the bolt body; S3. Mix the raw materials for the anti-corrosion layer, spray them on the surface of the bolt body, and obtain the corrosion-resistant bolt after drying.
[0024] Example 3 A corrosion-resistant bolt comprises a bolt body and an anti-corrosion layer on the surface of the bolt body, wherein the bolt body is composed of the following components by weight percentage: C 0.4%, Si 0.6%, Mn 2.2%, Ni 2.5%, Cr 0.5%, Mo 0.2%, Zn 0.5%, Nb 0.5%, V 0.1%, and the rest is iron and unavoidable impurities; The anticorrosive layer raw materials include the following components in parts by weight: 50 parts of water-based acrylic emulsion, 3 parts of zinc sulfate, 5 parts of isocyanate, 3 parts of hydroxypropyl methylcellulose, 5 parts of dimethylaniline, 9 parts of strontium titanate, 15 parts of zirconium oxide, 30 parts of mica powder, 0.8 parts of propylene glycol butyl ether, and 2 parts of vinyl triethoxy silane; The method for preparing the corrosion-resistant bolt comprises the following steps: S1. Mix carbon powder, ferrosilicon alloy, ferromanganese alloy, nickel powder, ferrochrome alloy, zinc block, ferrovanadium alloy, ferromolybdenum alloy and ferroniobium alloy according to the ingredients, and smelt and cast them to obtain steel ingots; S2. After forging, the steel ingot is normalized at 870°C for 60 minutes, quenched at 830°C for 50 minutes, tempered at 580°C for 60 minutes, and then drawn and threaded to obtain the bolt body; S3. Mix the raw materials for the anti-corrosion layer, spray them on the surface of the bolt body, and obtain the corrosion-resistant bolt after drying.
[0025] Example 4 The only difference between this embodiment and Embodiment 2 is that the bolt body is composed of the following components by weight percentage: C 0.3%, Si 0.4%, Mn 1.7%, Ni 2.0%, Cr 0.3%, Mo 0.11%, Zn 0.02%, Nb 0.04%, V 0.03%, and the rest is iron and unavoidable impurities.
[0026] Example 5 The only difference between this embodiment and Embodiment 2 is that the bolt body is composed of the following components by weight percentage: C 0.3%, Si 0.4%, Mn 1.7%, Ni 2.0%, Cr 0.3%, Mo 0.11%, Zn 0.03%, Nb 0.06%, V 0.03%, and the rest is iron and unavoidable impurities.
[0027] Example 6 The only difference between this embodiment and Embodiment 2 is that the bolt body is composed of the following components by weight percentage: C 0.3%, Si 0.4%, Mn 1.7%, Ni 2.0%, Cr 0.3%, Mo 0.11%, Zn 0.05%, Nb 0.1%, V 0.03%, and the rest is iron and unavoidable impurities.
[0028] Example 7 The only difference between this embodiment and Embodiment 5 is that the bolt body is composed of the following components by weight percentage: C 0.3%, Si 0.4%, Mn 1.7%, Ni 2.0%, Cr 0.3%, Mo 0.11%, Zn 0.07%, Nb 0.02%, V 0.03%, and the rest is iron and unavoidable impurities.
[0029] Example 8 The only difference between this embodiment and Embodiment 5 is that the bolt body is composed of the following components by weight percentage: C 0.3%, Si 0.4%, Mn 1.7%, Ni 2.0%, Cr 0.3%, Mo 0.11%, Zn 0.06%, Nb 0.03%, V 0.03%, and the rest is iron and unavoidable impurities.
[0030] Example 9 The only difference between this embodiment and Example 8 is that the mica powder is replaced by an equal amount of modified mica powder. The preparation method of the modified mica powder comprises the following steps: dissolving 1.5 g of 2-cyclohexylaminoethanesulfonic acid in 300 mL of methanol, adding 50 g of mica powder and mixing, heating to 50° C., stirring at this temperature for 6 hours, and obtaining the modified mica powder after drying.
[0031] Example 10 The only difference between this embodiment and Example 8 is that the mica powder is replaced by an equal amount of modified mica powder. The preparation method of the modified mica powder comprises the following steps: dissolving 2.5 g of 2-cyclohexylaminoethanesulfonic acid in 300 mL of methanol, adding 50 g of mica powder and mixing, heating to 60° C., stirring at this temperature for 3 h, and obtaining the modified mica powder after drying.
[0032] Comparative Example 1 The only difference between this comparative example and Example 1 is that the bolt body consists of the following components by weight: C 0.2%, Si 0.3%, Mn 1.0%, Ni 1.5%, Cr 0.1%, Mo 0.02%, Nb 0.006%, V 0.01%, and the rest are iron and unavoidable impurities.
[0033] Comparative Example 2 The only difference between this comparative example and Example 1 is that the bolt body consists of the following components by weight: C 0.2%, Si 0.3%, Mn 1.0%, Ni 1.5%, Cr 0.1%, Mo 0.02%, Zn 0.006%, V 0.01%, and the rest are iron and unavoidable impurities.
[0034] Comparative Example 3 The only difference between this comparative example and Example 1 is that the bolt body consists of the following components by weight: C 0.2%, Si 0.3%, Mn 1.0%, Ni 1.5%, Cr 0.1%, Mo 0.02%, Zn 0.001%, Nb 0.005%, and the rest are iron and unavoidable impurities.
[0035] Comparative Example 4 The only difference between this comparative example and Example 1 is that the bolt body consists of the following components by weight: C 0.2%, Si 0.3%, Mn 1.0%, Ni 1.5%, Cr 0.1%, Mo 0.02%, V 0.01%, and the rest are iron and unavoidable impurities.
[0036] Comparative Example 5 The only difference between this comparative example and Example 1 is that the bolt body consists of the following components by weight: C 0.2%, Si 0.3%, Mn 1.0%, Ni 1.5%, Cr 0.1%, Mo 0.02%, and the rest is iron and unavoidable impurities.
[0037] The tensile strength of the bolts prepared in Examples 1 to 8 and Comparative Examples 1 to 5 was measured according to the test method in GB / T 228.1-2021 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method"; the test results are shown in Table 1.
[0038] Table 1 Bolt strength performance test results
[0039] Compared with Example 1, the tensile strength of the bolts prepared in Comparative Examples 1 to 5 is lower than that in Example 1, indicating that adding Zn, Nb, and V simultaneously to the bolt body can improve the tensile strength of the bolt.
[0040] Compared with Example 2, the weight of Zn and Nb and the weight ratio to V were changed in Examples 4 to 6. As a result, the tensile strength of the bolts prepared in Examples 5 to 6 was higher than that in Example 2 and Example 4, indicating that when the weight of Zn and Nb and the weight ratio to V are 3 to 5:1, the tensile strength of the bolts can be further improved.
[0041] Compared with Example 5, the weight ratio of Zn to Nb was changed in Examples 7 to 8. As a result, the tensile strength of the bolt prepared in Example 8 was higher than that in Examples 5 and 7, indicating that when the weight ratio of the sum of Zn and Nb to V is 3 to 5:1 and the weight ratio of Zn to Nb is 2:1, the tensile strength of the bolt can be further improved.
[0042] The bolts prepared in Examples 8 to 10 were subjected to a corrosion resistance test: the bolts were immersed in a 15 wt % HCl aqueous solution for 60 min, and the weight loss rate of the bolts was tested; weight loss rate = (bolt weight before immersion - bolt weight after immersion) / bolt weight before immersion × 100%; the test results are shown in Table 2.
[0043] Table 2 Bolt corrosion resistance test results
[0044] Compared with Example 8, the weight loss rate of the bolts prepared in Examples 9 to 10 is lower than that in Example 2, indicating that adding mica powder modified with 2-cyclohexylaminoethanesulfonic acid to the anti-corrosion layer can improve the corrosion resistance of the bolts.
[0045] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A corrosion-resistant bolt, comprising a bolt body and an anti-corrosion layer on the surface of the bolt body, characterized in that: The bolt body is composed of the following components in weight percentage: C 0.2%~0.4%, Si 0.3%~0.6%, Mn 1.0%~2.2%, Ni1.5%~2.5%, Cr 0.1%~0.5%, Mo 0.02%~0.2%, Zn 0.001%~0.5%, Nb 0.005%~0.5%, V 0.01%~0.1%, and the rest is iron and inevitable impurities.
2. A corrosion-resistant bolt according to claim 1, characterized in that: The weight ratio of the Zn and Nb to the V is 3-5:
1.
3. A corrosion-resistant bolt according to claim 2, characterized in that: The weight ratio of the Zn to the Nb is 2:
1.
4. The method for preparing a corrosion-resistant bolt according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, after preparing the materials according to the components, smelting and casting to obtain a steel ingot; S2, the steel ingot is forged, heat treated, drawn and threaded to obtain a bolt body; S3, mixing the raw materials for the anti-corrosion layer, spraying them on the surface of the bolt body, and obtaining the corrosion-resistant bolt after drying.
5. The method for preparing a corrosion-resistant bolt according to claim 4, characterized in that: The raw materials of the anti-corrosion layer include the following components in parts by weight: 40-50 parts of aqueous acrylic emulsion, 1-3 parts of zinc sulfate, 3-5 parts of isocyanate, 1-3 parts of hydroxypropyl methylcellulose, 3-5 parts of dimethylaniline, 6-9 parts of strontium titanate, 10-15 parts of zirconium oxide, 20-30 parts of mica powder, 0.5-0.8 parts of propylene glycol butyl ether, and 1-2 parts of vinyl triethoxy silane.
6. The method for preparing a corrosion-resistant bolt according to claim 5, characterized in that: The mica powder is modified mica powder; the modified mica powder is obtained by modifying mica powder with 2-cyclohexylaminoethanesulfonic acid.
7. The method for preparing a corrosion-resistant bolt according to claim 6, characterized in that: The added amount of the 2-cyclohexylaminoethanesulfonic acid is 3% to 5% of the mass of the mica powder.
8. The method for preparing a corrosion-resistant bolt according to claim 6, characterized in that: The preparation method of the modified mica powder comprises the following steps: dissolving 2-cyclohexylaminoethanesulfonic acid in methanol, adding mica powder for modification, and drying to obtain the modified mica powder.
9. The method for preparing a corrosion-resistant bolt according to claim 4, characterized in that: The heat treatment includes normalizing, quenching and tempering.
10. The method for preparing a corrosion-resistant bolt according to claim 9, characterized in that: The normalizing temperature is 850-870°C, and the normalizing time is 60-80 min; the quenching temperature is 810-830°C, and the quenching time is 50-60 min; the tempering temperature is 570-580°C, and the tempering time is 60-70 min.